2020
DOI: 10.1108/gs-03-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Multicharacteristics optimization of electrical discharge micro hole drilling in Mg alloy using hybrid approach of GRA–regression–PSO

Abstract: PurposeMagnesium alloys are becoming prominent as an alternative to the permanent biomedical implants. In present work, electric discharge drilling (EDD) process has been investigated and optimized for ZM21 Mg alloy that can be used for producing perforated bone implants having geometrically precise micro holes.Design/methodology/approach Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The results showed that the suggested optimization approach may adapt to the automated environment in both scenarios of externally imposed material or processing performance. For optimizing the multi-objective performance of the circularity at the entrance, the hole overcut, and the circularity at the exit of drilled micro holes, a hybrid approach of the PSO integrating gray relational analysis was used in the process of micro hole drilling in Mg alloy [107]. Regarding the prediction of micro-hole quality (radial over-cutting, recast layer thickness, and MRR) on Inconel 718 superalloy treated by micro-EDM, Rao [108] suggested a prediction model based on the bionic intelligent hybrid algorithm.…”
Section: Parameters Optimizationmentioning
confidence: 99%
“…The results showed that the suggested optimization approach may adapt to the automated environment in both scenarios of externally imposed material or processing performance. For optimizing the multi-objective performance of the circularity at the entrance, the hole overcut, and the circularity at the exit of drilled micro holes, a hybrid approach of the PSO integrating gray relational analysis was used in the process of micro hole drilling in Mg alloy [107]. Regarding the prediction of micro-hole quality (radial over-cutting, recast layer thickness, and MRR) on Inconel 718 superalloy treated by micro-EDM, Rao [108] suggested a prediction model based on the bionic intelligent hybrid algorithm.…”
Section: Parameters Optimizationmentioning
confidence: 99%
“…There are two types of optimization techniques: the first one is statistical, and the second is an artificial intelligence technique. These include Taguchi technique [20][21][22][23], response surface methodology [24][25][26], gray relational analysis [27][28][29], utility concept [30], entropy measurement technique [31,32], genetic algorithm [33], non-dominated genetic algorithm [34,35], particle swarm optimization [36,37], teaching learning-based optimization [25], artificial neural network [38,39], gray wolf optimization [40,41], etc. The above-mentioned techniques are used for the planning of experiments, modeling, and optimization of the machining indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The grey system theory established by Professor Deng Julong provides a theoretical basis for studying the system of “partial information known and partial information unknown” (Deng, 1982). Its main research contents include grey algebra (Liu et al , 2010; Su et al , 2017; Aydemir, 2020; Mierzwiak et al , 2021), grey relational analysis (Yang et al , 2021a; Zhong et al , 2021; Cao et al , 2021), grey cluster (Luo et al , 2021), grey prediction (Li et al , 2021; Yang et al , 2021b; Quartey-Papafio et al , 2021), grey decision-making (Liu et al , 2017; Ma et al , 2021; Ali et al , 2022), grey control (Ahuja et al , 2021; Yang and Xue, 2017), grey programming (Mahmoudi et al , 2018; Asghari et al , 2021; Darvishi et al , 2021) and so on. Since the establishment of grey system theory, many scholars have paid great attention and obtained rich research results.…”
Section: Introductionmentioning
confidence: 99%